BABA, ŻABA I KROWA, CZYLI ROZWAŻANIA O TYM, JAK DAWNE SĄ LUDOWE WIERZENIA O ŻABIE WYSYSAJĄCEJ MLEKO KROWIE - WITCZAK, KRZYSZTOF TOMASZ (Slavia Occidentalis, 2020)
The aim of this paper is to demonstrate the archaic status of the Polish folk beliefs about certain amphibians (frogs, toads) and reptiles (snakes, lizards, salamanders) believed to have sucked milk from cows. Some Polish peasants were even convinced that milk cows loved suckers (esp. snakes, frogs) more than their calves. There are many folk tales where a witch or a mythical creature assumes the form of a armful animal to suck cow’s milk. The author demonstrates that the oldest part of these beliefs can be traced to the Proto-Indo-European cultural heritage. In fact, some Indo-European languages have preserved a clear indication of animal cow-suckers in their vocabulary, e.g. Ukr. молокосúс m. ‘lizard, salamander’ (literally ‘milk-sucker’); Lith. žaltỹs, žalktỹs m. ‘a not-venomous snake, esp. the grass snake, the slow worm’, Latv. zalktis, zaltis m. ‘snake’, Latg. zalkts m. ‘the grass snake’ (< PIE. *ĝolh2ktii̯os adj. ‘delighting in milk’ < PIE. *ĝl̥h2kt- n. ‘milk’); OInd. gōdhā́- f. ‘a big lizard’ (< PIE. *gu̯h3eu̯-dheh1- f. ‘a cow-sucker’, cf. PIE. *gu̯h3eu̯s f. ‘cow’ and *dheh1- ‘to suck’); Lat. būfō m. ‘a toad’ (< PIE. *gu̯h3eu̯-dhh1-ōn- m. ‘a cowsucker’); Alb. thithëlopë, also blloçkëlopë f. ‘common toad’ (literally ‘sucking/ chewing cows’); Hitt. akuu̯akuu̯aš c. ‘a toad’ (literally ‘sucking cows’, cf. Hitt. aku- ‘to drink’). It is assumed that the Indo-European beliefs were associated with breeding of cattle and were an attempt at a rational (or not) explanation of the alleged cause of poor lactation or cows’ milk loss. It is likely that the ailing animal was perceived as possessed by a demonic character, although the association of an animal with a witch or a devil was made relatively late and probably under the influence of beliefs from Western Europe.